Analysis of Made Lamongan Residential Drainage System Using SWMM (Storm Water Management Model) and HEC-RAS (Hydraulic Engineering Centre-River Analysis System) Models - Febrianto, Ridwan; Bisri, Mohammad; Cahya, Evi Nur (Civil and Environmental Science Journal (CIVENSE), 2023)
Made Lamongan Residential is located in an area that has a flat slope and is flanked by two rivers Kali Mengkuli and Kali Gorok, the problem in the study area is that the drainage system is unable to serve rainwater runoff. This is evidenced by the occurrence of inundation during the rainy season with high intensity. The height of the inundation that occurs in the Residential complex ± 60 cm with a reduction in inundation of more than 12 hours. The calculation results showed that there were several sections of the channel that occurred runoff with a planned Q5 flood discharge of 8.14 m3/sec. Based on the results of surveys in the field, many channels were found that had changed their dimensions due to the renovation of residents' houses. In this study, 1D channel hydraulic modelling was carried out using SWMM and HEC-RAS software to obtain a model that was close to the surface runoff conditions at the study site. The purpose of this study is to obtain the greatest handling of inundation in Made Residential in reducing the height of the inundation based on the model to be carried out, as well as obtaining the value of model calibration at the study site.